2017
DOI: 10.1038/srep46130
|View full text |Cite|
|
Sign up to set email alerts
|

Intestinal microbiome in children with severe and complicated acute viral gastroenteritis

Abstract: The aim of the present study was to evaluate the microbiota of children with severe or complicated acute viral gastroenteritis (AGE). To that end, next-generation sequencing (NGS) technology was used to sequence the 16S ribosomal RNA (16S rRNA) gene in 20 hospitalized pediatric patients with severe or complicated AGE and a further 20 otherwise healthy children; the fecal microbiome was then assessed. Comparative metagenomics data were analyzed by a Wilcoxon rank–sum test and hierarchical clustering analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 28 publications
8
64
2
Order By: Relevance
“…This investigation showed that the increased abundance of this bacterial taxon within this enterotype was unlikely to be due to the causative agent itself, given that isolates from confirmed cases of viral infection and non-Gammaproteobacteria bacterial infection were also classified within this enterotype. This is supported by a recent study that reported a significant increase in the richness of Enterobacteriaceae in morecomplicated cases of acute viral gastroenteritis compared to that in mild-to-moderate cases (8). We also observed that a more stringent analysis of the 16S rRNA gene sequences allowed the further differentiation of Escherichia-Shigella.…”
Section: Discussionsupporting
confidence: 88%
“…This investigation showed that the increased abundance of this bacterial taxon within this enterotype was unlikely to be due to the causative agent itself, given that isolates from confirmed cases of viral infection and non-Gammaproteobacteria bacterial infection were also classified within this enterotype. This is supported by a recent study that reported a significant increase in the richness of Enterobacteriaceae in morecomplicated cases of acute viral gastroenteritis compared to that in mild-to-moderate cases (8). We also observed that a more stringent analysis of the 16S rRNA gene sequences allowed the further differentiation of Escherichia-Shigella.…”
Section: Discussionsupporting
confidence: 88%
“…Another researcher found a significant negative linkage between Bifidobacterium and abdominal pain in adults with acute viral gastroenteritis. However, the above correlation cannot be copied in fecal samples of children with acute viral gastroenteritis (16). The possible explanation may be that the species and amounts of Bifidobacterium in the infant microbiota is not stable and alternates swiftly in comparison with adult microbiota (17).…”
Section: Introductionmentioning
confidence: 97%
“…Severe diarrhoea in AGE has a direct impact on the gut microbiome and causes a significant reduction in intestinal microbial diversity (Chen et al, 2017). A recent study characterising the microbiota of children with AGE has shown that greater microbiotal diversity correlates with faster clinical improvement.…”
Section: Acute Gastroenteritismentioning
confidence: 99%